Answer:
C
Step-by-step explanation:
Convert them all to the form y = mx + c
1)
4x + 3y = 15
3y = -4x + 15
y = -4/3 x + 5
2)
3x - 4y = -8
-4y = -3x - 8
4y = 3x + 8
y = 3/4x + 2
3)
y + 1 = 4/3(x - 6)
y + 1 = 4/3x - 8
y = 4/3x - 9
4)
y = 3/4x - 5
It’s solved by using the cosine rule
So for this, you will be doing two different multiplications: 3 x 4 and √8 x √3.
3 x 4 = 12
√8 x √3 = √24
Now our result is 12√24, however, this can be simplified. Using the product rule of radicals (√ab = √a x √b), our simplification is such:
12√24 = 12√(8 x 3) = 12√(4 x 2 x 3) = 2 x 12√(2 x 3) = 24√6
In short, the answer is 24√6, or the first option.
Eight more than the product of two and a number x
8+2x <== in mathematical form
Eight more= 8+
Product= multiply
number=x
~'Manda
The common factor of 5x2 is y5x